Voluntary exercise does not increase gastrointestinal motility but increases spatial memory, intestinal eNOS, Akt levels, and Bifidobacteria abundance in the microbiome - Bakonyi, Peter; Kolonics, Attila; Aczel, Dora; Zhou, Lei; Mozaffaritabar, Soroosh; Molnár, Kinga; László, Lajos; Kutasi, Balazs; Tanisawa, Kumpei; Park, Jonguk; Gu, Yaodong; Pinho, Ricardo A.; et al. (Frontiers in Physiology, 2023)
The interaction between the intestines and brain is a great puzzle since it is mediated by very complex mechanisms. Therefore, the possible interactions between the brain-exercise-intestinemicrobiome axis were investigated in control (C, N=6) and voluntary exercised (VE, N=8) middle-aged rats. Endurance capacity was assessed by VO2max on the treadmill, spatial memory by Morris Maze test, gastrointestinal motility by EMG, the microbiome by 16sRNAGene Amplicon Sequencing, caveolae by electron microscopy, and biochemical assays were used to measure protein levels and production of reactive oxygen species (ROS). Eight weeks of voluntary running increased VO2max, Spatial memory was assessed by the Morris maze test but did not significantly change the motility of the gastrointestinal tract and the production of ROS in the intestine. The protein kinase B (Akt) and Endothelial nitric oxide synthase (eNOS) protein levels increased significantly in the intestine, while Peroxisome proliferatoractivated receptor gamma coactivator 1-alpha (PGC-1α), Mitochondrial transcription factor A (TFAM), Nuclear respiratory factor 1 (NFR1), SIRT1, SIRT3, Nicotinamide phosphoribosyl transferase (NAMPT), and nuclear factor (NF)-κB did not change. On the other hand, VE increased the number of caveolae in the smooth muscle of the intestine and the relative abundance of Bifidobacteria in the microbiome, which correlated with Akt levels in the intestine. VE exercise has systemic effects and the relationship between the intestinal Akt and the microbiome of the gastrointestinal tract could be an important adaptive response.